Computer-Mediated Sharing Circles for Intersectional Peer Support with Home Care Workers. - Poon, Anthony.; Luebke, Matthew.; Loughman, Julia.; Lee, Ann.; Guerrero, Lourdes.; Sterling, Madeline.; Dell, Nicola. (Tufts University. Tisch Library., 2023)
Keywords: healthcare, home care workers, mutual help, peer support, practitioners, professionalization, safe spaces, sharing circles, support groups.; Topic: Human-centered computing / Collaborative and social computing / Empirical studies in collaborative and social computing; Topic: Human-centered computing / Collaborative and social computing / Collaborative and social computing theory, concepts and paradigms / Computer supported cooperative work; Topic: Social and professional topics / User characteristics; Topic: Human-centered computing / Collaborative and social computing / Collaborative and social computing theory, concepts and paradigms / Social engineering (social sciences); Topic: Human-centered computing / Collaborative and social computing / Collaborative and social computing systems and tools / Social networking sites; ACM Open.